Efficacy and Safety of Radiofrequency Ablation and Trendelenburg Procedure for Varicose Vein Treatment in a Tertiary Care Hospital - Rathnaganpathi Thulasikumar; Mahesh Gogineni; Manoj Prabakar Ravichandran; Marun Raj Gunasekaran; SR Subrammaniyan (Indian Journal of Vascular and Endovascular Surgery)
Context: Varicose veins have been conventionally treated by Trendelenburg procedure, which includes below-knee phlebotomies, juxta-femoral flush ligation of saphenous veins, and below-knee vein stripping. However, radiofrequency ablation (RFA) therapy, a less invasive method that uses high-frequency alternating current to cause thermal damage to the venous tissue, has become increasingly popular due to its reduced adverse effects. This study aimed to compare these two methods regarding early ambulation, return to work, postoperative pain severity, recovery time, and complication rates. Aims: To compare the effectiveness and safety of open procedure compared to endovenous ablation. Settings and Designs: An analytical cross-sectional study was prospectively conducted at Saveetha Medical College in Chennai. Subjects and Methods: This analytical cross-sectional study, conducted prospectively from May 2020 to May 2023, involved 100 individuals diagnosed with varicose veins. Participants were followed up at 3-, 6-, and 12-month intervals. The study was carried out at Saveetha Medical College in Chennai. Fifty patients were treated using the Trendelenburg method (Group I), while 50 patients received RFA (Group II). The data on early ambulation, return to work, postoperative pain severity, recovery time, and complication rates were collected and analyzed using the Epi Info 7 version. Results: Group I did not show any significant complications, such as bleeding, hematoma, or inflammation, compared to Group II. Notably, in Group II, there was an earlier hospital discharge, faster return to daily activities and work, and faster patient mobilization. Conclusions: This study concludes RFA, compared to the Trendelenburg method, has early ambulation, early return to work, reduced postoperative pain, swift recovery, and fewer complications. Consequently, we recommend RFA as their primary surgical option for patients with varicose veins in the lower limbs.